Association between regular breakfast consumption and academic performance among 6th-grade elementary school male students in Makkah, Saudi Arabia - Alruwaili, Fahad Khulaif; Khan, Adeel Ahmed; Alruwaili, Amal; Alruwaili, Wardah; Alruwaili, Fahdah (Journal of Contemporary Medical Sciences, 2023)
Objectives: To determine the association between regular breakfast consumption and academic performance among 6th-grade elementary school male students in Makkah, Saudi Arabia. Methods: Our cross-sectional study used a questionnaire for public and private elementary school children in Makkah, Saudi Arabia. Participants with known mental retardation, language barriers, and chronic diseases were excluded. The data analysis was performed using IBM SPSS V.26. Results: In our study, 412 students were included. Most students (74.3%) obtained a high final degree between 80 - 100%. Most students (67.2%) believed having breakfast helps in obtaining high degrees. In addition, those who never had breakfast had a lower academic degree (p-value <0.001). Conclusion: The results of our study emphasized the significance of having breakfast on a daily basis for academic success, as students who reported consuming breakfast regularly were found to be more likely to achieve high academic scores.